A Vision of Tourism Sector in India - Joseph, Jelsy; Adalarasu, B. (Indian Journal of Marketing, 2008)
India's amazing diversity offers you everything you could ever want in a holiday. The moment a person sets foot in India, he is greeted by a graceful namaste, a gesture that denotes both welcome and respect. The rate of success in the tourism sector is highly influenced by the instrumentality of supporting industries, such as hotel, transporation, communication, banking or so. Hence, due to the possibility of vast development in these fields, there is a tremendous scope for tourism in India. Overseas banks are opening their operations in India, which attracts the foreigners to fly to India. Hotel and transportation facilities in India are growing day by day with international standards to attract the traveller savvy worldwide.